Performing Authenticity: Participatory Representation and Power in Ethnic Themed Musicals - Kusumadewi, Kenya Permata; Zainsty, Arly Yanatri (Indonesian Scientific Publication, 2025)
Contemporary musical films are increasingly being used as vehicles for ethnic storytelling. This study investigates how industry practices specifically casting, creative participation, cultural consultation, and marketing strategies shape the authenticity and reception of ethnic representation in four case studies: In the Heights, Coco, Encanto, and West Side Story (2021). Using a comparative content analysis approach informed by boundary making theory and representation studies, the research triangulates production documents, promotional materials, and reception data to examine how participatory inclusion influences narrative integrity. Methodologically, the study applies a multimodal coding framework to assess how structural dynamics influence storytelling from development through distribution. It incorporates data from creative personnel profiles, marketing discourse, and community feedback, enabling a comprehensive understanding of industry driven representation. The results reveal that films involving creators and consultants from target communities tend to offer richer, more nuanced portrayals, while those relying on symbolic inclusion or commodified authenticity risk critical backlash and community disengagement. Casting misalignments, marketing inconsistencies, and lack of structural inclusion are identified as recurring challenges. These findings highlight the need for systemic reform in media production to promote authentic and accountable ethnic storytelling. The study contributes to scholarly debates on cultural representation and offers a replicable model for evaluating equity in media narratives.